Source Term Analysis of Long-Life 620 MWt BWR During Loss of Coolant Accident (LOCA) - Hidayati Amar; Zaki Su’ud; Ari Ari Pasek (Institut Teknologi Bandung, 2011)
Source term analysis on a long-life 620 MWt BWR has been performed. The study includes fuel cell calculations, multi-groups diffusion equation calculation with 8 groups of energy, source term calculation and dose calculation. The scope of the source term analysis includes fission product inventories calculation in core, their activity and their toxicity during the Loss of Coolant Accident (LOCA). The calculation based on the assumption that the reactor has been operating for 10950 days or 30 years with full power of 620 MWt. The total activity of the core is 1,12x109 Ci, and the higher inventory of the core is dominated by the trans-uranium elements. The release of fission product activity to the atmosphere is 1,11x107 Ci. And the toxicity analysis shows that noble gas has the higher toxicity degree. Whole body dose calculation result in exclusion zone is 7.17x10-04 rem and the thyroid dose calculation result in this zone is 7.21x10-02 rem. And for the whole body dose calculation result in low population zone is 2.69x10-05 rem and the thyroid dose calculation result in this zone resulted 1.80x10-03 rem.